Enhancing positive parent-child interactions and family functioning in a poverty sample: a randomized control trial - Negrão, Mariana (2014)
This study tested the attachment-based intervention program Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline (VIPP-SD) in a randomized controlled trial with poor families of toddlers screened for professional's concerns about the child's caregiving environment. The VIPP-SD is an evidence-based intervention, but has not yet been tested in the context of poverty. The sample included 43 families with 1- to 4-year-old children: mean age at the pretest was 29 months and 51% were boys. At the pretest and posttest, mother-child interactions were observed at home, and mothers reported on family functioning. The VIPP-SD proved to be effective in enhancing positive parent-child interactions and positive family relations in a severely deprived context. Results are discussed in terms of implications for support services provided to such poor families in order to reduce intergenerational risk transmission.